F8. ELECTRORETINOGRAPHIC CHANGES IN RESPONSE TO REWARD IN SCHIZOPHRENIA. (9th April 2019) - Demmin, Docia; Mote, Jasmine; Beaudette, Danielle; Silverstein, Steven
Abstract: Background: Dysfunction in CNS dopaminergic activity is thought to be related to specific impairments in schizophrenia, such as deficits in reward processing. Electroretinography (ERG) is a technique used to record retinal signaling, including waveforms thought to depend strongly on dopamine circuitry within the retina and/or changes in brain dopaminergic activity. Methods: In this ongoing study, we are using flash ERG to compare retinal responses of schizophrenia patients (SZ; n = 9) and healthy controls (HC; n = 15) at baseline, prior to (anticipatory pleasure), and after (consummatory pleasure), receiving a food reward. The primary variable of interest is light-adapted b-wave amplitude, reflecting the cone-driven bipolar cell response. Results: Across all time points (i.e., baseline, anticipatory, consummatory), SZ patients demonstrated significantly attenuated b-wave amplitudes compared to the HC group (ds = .75 to .96). There were significant differences in baseline vs. anticipatory (p = .046), anticipatory vs. reward (p = .002), and baseline vs. reward (p < .001) b-wave amplitudes in the HC group, but not the SZ group. SZ patients reported significantly more negative affect (d = 1.56) than the HC group, but groups did not differ significantly in reported positive emotion (Positive and Negative Affect Schedule [PANAS]). In the HC group, Temporal Experience of Pleasure Scale (TEPS) total scores correlated significantly with b-wave amplitudes at all three time points (ps = .015 to .025), but there were no significant relationships with TEPS scores and b-wave amplitudes in the SZ group. Discussion: These data replicate prior findings of attenuated bipolar cell activity in schizophrenia, and links between bipolar cell activity and reward in non-psychiatric samples but suggest a lack of relationship between these phenomena in schizophrenia.